2021
DOI: 10.3389/fmicb.2021.763288
|View full text |Cite
|
Sign up to set email alerts
|

Histone-Like Nucleoid Structuring Protein Modulates the Fitness of tet(X4)-Bearing IncX1 Plasmids in Gram-Negative Bacteria

Abstract: The emergence of plasmid-mediated tigecycline resistance gene tet(X4) poses a challenging threat to public health. Based on the analysis of tet(X4)-positive plasmids in the NCBI database, we found that the IncX1-type plasmid is one of the most common vectors for spreading tet(X4) gene, but the mechanisms by which these plasmids adapt to host bacteria and maintain the persistence of antibiotic resistance genes (ARGs) remain unclear. Herein, we investigated the underlying mechanisms of how host bacteria modulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 59 publications
(73 reference statements)
0
8
0
Order By: Relevance
“…The tet (X) gene and its variants were present in 23 countries on six continents ( Pan et al, 2020 ; Wang J. et al, 2021 ), which are also widely present in various bacterial species, including R. anatipestifer , E. coli , Acinetobacter , K. pneumoniae , Salmonella , Proteus , La Providencia bacteria, Bacteroides bacteria , Pseudomonas bacteria , and Aeromonas caviae ( Chen et al, 2019a , 2020 ). Moreover, most of the tet (X4) genes are located on different types of plasmids such as IncQ1, IncX1, IncFIB, IncHI1, F-:A18:B-, ColE2-like, IncN, p0111 and hybrid plasmids ( Fang et al, 2020 ), among which the IncX1 type is the most common ( Cai et al, 2021 ; Cui et al, 2022 ). The Nomenclature Center 1 recommends that only tet (X) will be used in the future, because the tet (X) gene variant DNA similarity is in the range of 83–100% among tet (X2)- tet (X14), corresponding amino acid similarity is between 82 and 100%, which is greater than the standard of 79% amino acid similarity.…”
Section: Prevalence Of Tet (X4)mentioning
confidence: 99%
“…The tet (X) gene and its variants were present in 23 countries on six continents ( Pan et al, 2020 ; Wang J. et al, 2021 ), which are also widely present in various bacterial species, including R. anatipestifer , E. coli , Acinetobacter , K. pneumoniae , Salmonella , Proteus , La Providencia bacteria, Bacteroides bacteria , Pseudomonas bacteria , and Aeromonas caviae ( Chen et al, 2019a , 2020 ). Moreover, most of the tet (X4) genes are located on different types of plasmids such as IncQ1, IncX1, IncFIB, IncHI1, F-:A18:B-, ColE2-like, IncN, p0111 and hybrid plasmids ( Fang et al, 2020 ), among which the IncX1 type is the most common ( Cai et al, 2021 ; Cui et al, 2022 ). The Nomenclature Center 1 recommends that only tet (X) will be used in the future, because the tet (X) gene variant DNA similarity is in the range of 83–100% among tet (X2)- tet (X14), corresponding amino acid similarity is between 82 and 100%, which is greater than the standard of 79% amino acid similarity.…”
Section: Prevalence Of Tet (X4)mentioning
confidence: 99%
“…Bacterial swimming motility is related to the invasiveness and adhesion ability [ 15 ], and a pervious study suggested that the introduction of exogenous tet (X4)-bearing plasmids may have an impact on bacterial movement ability [ 16 ]. Therefore, we compared the changes of motility in these tested strains after acquiring tet (X4)-bearing plasmids.…”
Section: Resultsmentioning
confidence: 99%
“…Given that both pig E. coli and chicken E. coli in this study were isolated before 2016, it is necessary to expand the range of tested host bacteria to get a deeper understanding in the future research. Biofilm formation ability and swimming motility serve as important indicators for bacterial adaptation and virulence [ 16 ], among which biofilm can assist bacteria to withstand environmental pressure [ 20 ] and swimming motility is associated with bacterial invasiveness and adhesion [ 15 ]. In this study, chicken E. coli generally displayed better biofilm formation ability and motility, implying chicken E. coli may be more threating after obtaining tet (X4)-plasmids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, suggesting that elimination of MTR genes from the environment would be difficult if not practically impossible even after the withdrawal of TETs/TIG. The involvement of plasmid-encoded histone-like nucleoid-structuring (H-NS) protein in modulating the fitness of tet (X4)-bearing plasmids (such as IncX1) and ensuring the persistence of the gene have been reported ( Cai et al, 2021 ). More critical is the situation where the transfer of tet (X4) resulted to increased size of transconjugant’s plasmid, thus, making it increasingly bigger than plasmids of the parental strain ( Li et al, 2020 , 2021d ).…”
Section: Distribution Reservoirs and Traits Of Mobile Tigecycline Res...mentioning
confidence: 99%